Guanine tracts enhance sequence directed DNA bends. - Milton, D L (1990)
Synthetic DNA fragments were constructed to determine the effect of G tracts, in conjunction with periodically spaced A tracts, on DNA bends. Relative length measurements showed that the G tracts spaced at the half helical turn enhanced the DNA bend. When the G tract was interrupted with a thymine or shortened to one or two guanines, the relative lengths decreased. If the G tract was replaced with either an A tract or a T tract, the bend was cancelled. Replacement with a C tract decreased the relative length to that of a thymine interruption suggesting that bend enhancement due to G tracts requires A tracts on the same strand.